IMMUNE SYSTEM PROBLEMS - Mustayev Shahjakhan; Mirzayev Saidakhror; Azimova Aziza (Journal of new century innovations, 2022)
Abstract: Also, sometimes your immune system mounts an attack when there is no invader or doesn’t stop an attack after the invader has been killed. These activities result in such problems as autoimmune diseases and allergic reactions.